2023
DOI: 10.1093/pnasnexus/pgad053
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ice sheet conservation using seabed anchored curtains

Abstract: Sea level rise is expected to be rapid and extremely damaging to coastal communities and infrastructure, with unavoidable losses and coastal protection costs in the tens of billions per year. Retreat of the Thwaites and Pine Island Glaciers is likely already in an unstable regime as their oceanic fronts are ablated by deep intruding layers of relatively warm seawater. Warm water can be blocked from reaching the grounding line by thin flexible buoyant curtains anchored to the seabed. The consequent reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Wolovick and Moore ( 17 ) proposed using solid artificial sills to block warm water from reaching the grounding line; using a simple model of ice flow and basal melting, they found that reductions in the basal melt rate could cause the floating ice shelf to thicken and flow outward, ultimately regrounding on the sill, which increased buttressing, reduced ice flux across the grounding line, and stabilized the ice sheet. In a companion paper ( 18 ), we improve on the ( 17 ) design by introducing the idea of buoyant underwater curtains. These are flexible impermeable curtains anchored to the seabed and held upright in the water column by their own buoyancy.…”
mentioning
confidence: 99%
“…Wolovick and Moore ( 17 ) proposed using solid artificial sills to block warm water from reaching the grounding line; using a simple model of ice flow and basal melting, they found that reductions in the basal melt rate could cause the floating ice shelf to thicken and flow outward, ultimately regrounding on the sill, which increased buttressing, reduced ice flux across the grounding line, and stabilized the ice sheet. In a companion paper ( 18 ), we improve on the ( 17 ) design by introducing the idea of buoyant underwater curtains. These are flexible impermeable curtains anchored to the seabed and held upright in the water column by their own buoyancy.…”
mentioning
confidence: 99%